NECK CIRCUMFERENCE AND CARDIAC RISK FACTOR IN ELDERLY MEN (Fiep Bulletin - online, 2016)
Introduction: Anthropometric indicators are increasingly being used, seeking more directed to the likelihood of countless risk factors responses. Neck circumference is one of these measures has been used for this purpose (Pitanga., 2005; Cornier et al, 2011). The NC (neck circumference) has been identified in the scientific literature as a simple measure, which allows the identification of overweight and obesity and to be positively correlated with changes in some metabolic syndrome factors. Objective: To investigate the relationship between CP and the waist risk factor for CVD. Method: A total of 85 individuals with 69.55 ± 5.89 years residents in Greater Victoria, was applied the paired Student t test. The WC classification is given from the values:
Keywords: Risk factors; elderly.